2007
DOI: 10.1590/s0036-46652007000200001
|View full text |Cite
|
Sign up to set email alerts
|

Cryoglobulinemia in chronic hepatitis C: clinical aspects and response to treatment with interferon alpha and ribavirin

Abstract: MC represents a prevalent complication in patients with CHC, specially older and cirrhotic patients. Only 24% of these patients show clinical manifestation of the disease, specially those with type II MC. The presence of MC did not affect the response to therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
2
1
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 30 publications
0
2
1
1
Order By: Relevance
“…Parise et al . reported that serum HCV RNA and HCV genotype did not have any association with cryoglobulinemia in CHC patients . However, we found that lower HCV RNA was associated with cryoglobulinemia but not HCV genotype 1.…”
Section: Discussioncontrasting
confidence: 75%
“…Parise et al . reported that serum HCV RNA and HCV genotype did not have any association with cryoglobulinemia in CHC patients . However, we found that lower HCV RNA was associated with cryoglobulinemia but not HCV genotype 1.…”
Section: Discussioncontrasting
confidence: 75%
“…The association between cryoglobulins and a specific genotype varies from one region to another and results from an interaction betwen viral and host factors. The high frequency of cryoglobulins in patients with genotype 3 infection observed in our study could have resulted from hight frequency of cirrhosis associated with this genotype, since crioglobulinemia may represent a complication in patients with HCV infection, especially in those with cirrhosis [ 16 , 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…В других исследованиях определена связь КГЕ с женским полом, не первым генотипом вируса, низкой вирусной нагрузкой и низким уровнем тромбоцитов [13], длительностью ВГC-инфекции [14], более высокой стадией фиброза и циррозом печени [15]. В отдельных исследованиях не было обнаружено взаимосвязи между КГЕ, уровнем РНК ВГC и генотипом вируса [16].…”
Section: Discussionunclassified